Time-motion analysis procedure in team sports: Example for youth basketball. - Canovas Lopez, M.; Arias, J. L.; Garcia Marin, P.; Yuste, J. L. (Strength and Conditioning Journal, 2014)
Coaches have always been interested in the physical demands that relate to the conditioning of athletes to play sports. During the past decade, researchers have focused on the analysis of actual game demands by means of time-motion analysis. The goal of this article is to present a procedure to obtain time-motion data in team sports.